Peningkatan Kecerdasan Emosional Siswa Melalui Pendekatan Analisis Transaksional - Yunita, Yunita; Wijaya, Wijaya; Misnaini, Sari (Sekolah Tinggi Agama Islam (STAI) Bumi Silampari, 2022)
Education is an effort that aims to develop a complete human being which includes three aspects, namely cognitive, affective and psychomotor aspects. To be able to achieve the educational goals which consist of these three aspects, it is necessary to develop various aspects of personality, including intellectual, social, and emotional. Individuals have two intelligences, namely thinking (intellectual intelligence) and feeling (emotional intelligence). Behaviors that refer to indications of low emotional intelligence of students such as not going to school without explanation, arriving late, fighting, saying rude / dirty words, not listening to the teacher during class, lying and fighting against the teacher. This study aims to determine the increase in students' emotional intelligence through a transactional analysis approach. The method used in this study is the Classroom Action Research method with 8 students as the research subject indicated low self-emotional intelligence. The implementation of the research consisted of three cycles, where each cycle consisted of four stages, namely planning, implementing actions, observing and reflecting. The results showed that in cycle 1 there was an average increase in counselee's emotional intelligence of 87.20%, in cycle 2 there was an increase in counselee's emotional intelligence an average of 96.71%, and cycle 3 there was an average increase of 94.53% of counselee's emotional intelligence. From cycle 1 to cycle 3, it shows that there is an increase in students' emotional intelligence through transactional analysis counseling techniques of 84.87%. It was concluded that there was an increase in emotional intelligence from 8 counselees after being given counseling techniques with a transactional analysis approach, the average increase in each counselee was different, in each cycle, the counselee's response to knowing self-emotions, managing self-emotions, motivating oneself, empathy and skills social fluctuations. It is expected that guidance and counseling teachers in madrasas can use transactional analysis techniques in improving students' emotional intelligence.